Phase Engineering of Iron–Cobalt Sulfides for Zn–Air and Na–Ion Batteries - Lu, Shu; Jiang, Jun; Yang, Hai; Zhang, Ying-Jie; Pei, Dan-Ni; Chen, Jie-Jie; Yu, Yan (ACS nano, 2020)
Rechargeable batteries are promising platforms for sustainable development of energy conversion and storage technologies. Highly efficient multifunctional electrodes based on bimetallic sulfides for rechargeable batteries are extremely desirable but still challenging to tailor with controllable phase and structure. Here, we report a colloidal strategy to fabricate FeCo-based bimetallic sulfides on reduced graphene oxide (rGO), which are expected to display highly efficient oxygen electrocatalysis and sodium storage performances. Specifically, as-screened FeCo8S8 nanosheets (NSs) on rGO originating from suitable tailoring of the Co9S8 matrix with Fe at the atomic level exhibited a very low potential difference (0.77 V) at 10 mA cm–2 and negligible voltage loss after 200 cycles as an air electrode for Zn–air batteries. For Na–ion batteries, FeCo8S8 NS/rGO demonstrated a superior high-rate capability (188 mAh g–1 at 20 A g–1) with long-term cycling stability. The bifunctional electrocatalytic property and sodium storage performance are attributed to not only the synergistic effect of Fe/Co but also the optimized catalytic activity and ion transport ability by the in situ rGO hybrid. This work demonstrates the potential applications of FeCo-based bimetallic sulfides as efficient electrode materials for both rechargeable Zn–air and Na–ion batteries.